Sociodemographic Factors and Policy Implications for Improved Food Security - Tri Wahyu Cahyono; Hiromi Tokuda (Pusbindiklatren Bappenas, 2024)
Ensuring food security is a pressing challenge facing East Kalimantan, and practical solutions are necessary. With the impending relocation of Indonesia's capital to this region, it's crucial to evaluate the area's food security in light of projected population growth and economic shifts. Prior to the new capital city project, it's essential to understand East Kalimantan's socio-economic factors to develop policies that strengthen food security for the future. This research uses logistic regression to analyze data from the Food Insecurity Experience Scale (FIES) module of the 2021 National Socio-Economic Survey (Susenas-BPS). The results show that 14.75% of households experience food insecurity, while 85.25% maintain food security. Factors such as education, family size, land ownership, marital status, employment, residence, and retirement security influence food security status significantly. However, age, gender, and home ownership have little impact. Notably, agricultural workers are more likely to experience food insecurity, while education and land ownership correlate with higher food security. Additionally, larger families are more vulnerable to food insecurity.